Malnutrition risk and effect of nutrition intervention among elderly in community - Norain Zainudin (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2021)
Malnutrition is a concern around the globe including in Malaysia due to its negative effects to the health of elderly. Nutrition screening can help to identify malnutrition and subsequent interventions can be provided to overcome health deterioration related to malnutrition. This study aimed to identify the prevalence of malnutrition and associated factors, dietary intake and effectiveness of nutrition intervention among elderly living in the community. In Phase I of the study, a total of 413 participants aged 60 years and above in several agricultural settlements around Kuantan, Pahang was recruited (n= 134 men, n= 279 women). Malnutrition risk was evaluated using the Mini Nutritional Assessment Short Form (MNA-SF), whilst functional status was determined using Instrumental Activities of Daily Living (IADL). Mini Mental State Examination (MMSE) and Geriatric Depression Scale (GDS) were used to identify cognitive impairment and depressive symptom of participants respectively. Dietary intake data were collected with the use of diet history method and analyses were performed using Nutritionist Pro Software. Adequacy of participants' dietary intake was assessed against Recommended Nutrient Intakes for Malaysia (RNI) 2017. Phase II of the study evaluated the effectiveness of nutrition intervention on nutritional status and dietary intake of the elderly after three months. The elderly who were at malnutrition risk were grouped into intervention (n=30) and control groups (n=30). The intervention group received intensive nutrition intervention while the control group received individual dietary consultation only. Statistically significant value was set at p<0.05. This study revealed that 5.1% of elderly participants were malnourished, whilst 20.6% of them were at risk of malnutrition. Age, smoking status, income level, living status and depression were significantly associated with malnutrition risk. This study found that mean energy, protein and fiber intake were significantly lower than recommendation in both genders except for fat and carbohydrate. Micronutrients intake including calcium, vitamin A, vitamin C, vitamin D, riboflavin, thiamine, iron and folate did not meet the requirement outlined in RNI with statistically significant differences. In addition, energy, carbohydrate, protein, fat, folate and iron intake were significantly higher in male than female participants. Meanwhile, calcium and vitamin A intake were significantly higher in female than male participants. Phase II of the study demonstrated that nutrition intervention could help to improve nutritional status of the elderly living in the community. Mean MNA-SF score, body weight, energy, carbohydrate and fiber intake of intervention and control groups improved significantly after three-month follow-up. Mean MNA-SF score of intervention group was identified in well-nourished category after three months which indicated greater impact of intensive nutrition intervention. In conclusion, this study showed malnutrition was prevalent among elderly living in the community while inadequate dietary intake was also an issue in this population. The findings contribute to the body of evidence that nutrition screening is an important initial step to identify malnutrition risk among community living elderly and appropriate intervention is vital to improve their nutritional status. Multidisciplinary healthcare professional collaboration is warranted in future research to identify malnutrition problems and provide effective measures for nutritional care of the elderly.